Educational Challenges and Motivational Orientations in College Students from the Health Sciences Department during the COVID-19 Pandemic - Olguín López, Alma Yasmin (2023)
Online classes have become one of the main teaching methods in higher education during the pandemic, which has forced students to adapt themselves to keep their motivation in the face of different educational challenges that have not been fully resolved. The objective of the study was to describe the educational challenges and motivational orientations of college nursing students during the COVID-19 pandemic. Through a descriptive type design, the researchers applied a standardized questionnaire to 300 Mexican university students. As the main discoveries, it was found that students mostly face technological challenges, followed by socio-affective ones. However, the motivational orientation towards learning predominates among students, where the educational context is a determinant of the teaching-learning process. Hence, the authors concluded that motivation (learning orientation) favors learning and acts as an essential intermediary during online learning. Moreover, the transfer from face-to-face education to online teaching has complicated the processes of integration and adaptation for students. The former occurs while educational challenges have become more acute in a pandemic context, and where technological and socio-affective categories represent the elements students must face. Therefore, the researchers recommend a correlational study to provide a better understanding of the possible relationship between the two studied variables. In addition, in the future, different qualitative methods could be used to further explore the meaning of different motivational orientations in online educational environments under different conditions.